From the editors - Editors (ERDKUNDE, 2023)
When we decided a few years ago to establish an online platform for the journal Erdkunde and ultimately to develop the journal into an open access journal, it was predictable that this decision would have an impact on subscriptions to the print edition. We have now reached the point where continuing the print edition no longer seems viable and have therefore decided to discontinue the print edition of Erdkunde and to continue the journal as a purely open access online journal starting with volume 78 (2024). As of January 2024, Erdkunde has a new subtitle to better capture the content. The previous subtitle "Archive for Scientific Geography" occasionally led to ambiguities and misunderstandings and did not clearly indicate that the journal was intended as a platform for the whole spectrum of physical geography, human geography or their intersections. We decided that the new subtitle of Erdkunde from January 2024 and onwards will be: Journal of Human and Physical Geographies